Identification of Factors that Influence the Attitude of the Millenial Generation towards Interest to Buy Counterfeit Products on the Online Marketplace - Wulan Sastika; Laurentia Verina Halim Secapramana (Budapest International Research and Critics University, 2022)
The current global era has entered the era of the industrial revolution 4.0 along with increasingly rapid technological developments, one of which is the rapid development of the internet so that many online marketplaces appear. Along with the emergence of the COVID-19 outbreak, many people prefer online shopping. There is a demand to buy fashion products, most people make imitation fashion products the main alternative. One of the targets is the millennial generation, which currently dominates in number. The purpose of this study is to determine the effect of value consciousness, brand consciousness, perceived risk, materialsm, social influence, status consumption, integrity towards attitude towards counterfeit for shopping in online marketplaces. The data used in this study is primary data taken from a questionnaire. The respondents are 200 respondents who are millennials who have an online marketplace account and have purchased counterfeit products in the online marketplace. This study uses a quantitative approach with the method of Structural Equation Modeling (SEM). SEM analysis using the AMOS 22 program. The results of this study indicate that value consciousness, materialsm and social influence have a positive effect on attitude towards counterfeit. Meanwhile brand consciousness, status consumption, and integrity have no effect on attitude towards counterfeit and perceived risk has a negative effect on attitude towards counterfeit. And in this study there is a moderator variable income.